The Effects of Legal Regime on the Patterns of Stock Returns around ADR Earnings Announcements - Kang, Tony (Institutional Knowledge at Singapore Management University, 2003)
This study examines the effects of legal regime on the patterns of stock returns surrounding the earnings announcements of American Depositary Receipt (ADR) programs. My results indicate that the properties of accounting earnings associated with the local legal regime of an ADR program spill over to U.S. GAAP reconciled earnings. In particular, I find that the market reacts significantly to the earnings announcements of the ADR programs from common law countries whose accounting earnings are known to be more conservative and timely, but not to those of the ADR programs from code law countries where the earnings are known to be less conservative and timely.